Penjernihan Ekstrak Etanol Daun Bidara Arab (Ziziphus spina-christi L.) dan Rimpang Kunyit (Curcuma longa L.) dengan Elektrokoagulasi - Fida Surtiniyati Shofia; Gita Cahya Eka Darma; Sani Ega Priani (Bandung Conference Series: Pharmacy, 2023)
Abstract. The use of ethanol extracts of arabian bidara leaves and turmeric rhizomes as plants that provide pharmacological effects has been widely used in the pharmaceutical industry. Plant extracts either as active or additives ingredients usually have an effect on a product in the form of a color display that matches the color of extract. The color intensity of extracts often interferes in the manufacturing stage to the evaluation of pharmaceutical products. To overcome this problem, clearing of plant extracts using electrocoagulation was carried out. This study aims to clearing the ethanol extracts of arabian bidara leaves and turmeric rhizomes using electrocoagulation as a method to reduce the intensity of extracts or obtain clearer extracts. The extraction clearing was performed using electrocoagulation with copper as the electrode. The results showed that the samples treated with electrocoagulation treatment had a cleare sample color, the ethanol extracts sample of arabian bidara leaves had a clear light brown color, while the ethanol extract sample of turmeric rhizome had a clear brown-red color. Therefore, electrocoagulation could be used to clearing the ethanol extracts of arabic bidara leaves and turmeric rhizomes. Keywords: Clearance of extracts, Ziziphus spina-christi, Curcuma longa. Abstrak. Penggunaan ekstrak etanol daun bidara arab dan rimpang kunyit sebagai tanaman yang memberikan efek farmakologis telah banyak digunakan di industri farmasi. Ekstrak tanaman baik sebagai bahan aktif atau tambahan biasanya memberikan pengaruh terhadap suatu produk berupa tampilan warna yang sesuai dengan warna ekstrak. Kepekatan warna ekstrak sering menjadi masalah dalam tahap pembuatan hingga evaluasi produk farmasi. Untuk mengatasi masalah tersebut dapat dilakukan penjernihan ekstrak tanaman menggunakan elektrokoagulasi. Penelitian ini bertujuan untuk menjernihkan ekstrak etanol daun bidara arab dan rimpang kunyit menggunakan elektrokoagulasi sebagai salah satu metode untuk mengurangi kepekatan ekstrak atau memperoleh ekstrak yang lebih jernih. Penjernihan ekstrak dilakukan menggunakan elektrokoagulasi dengan tembaga sebagai elektroda. Hasil penelitian menunjukan bahwa sampel dengan perlakuan elektrokoagulasi memiliki warna sampel yang lebih jernih, dimana sampel ekstrak etanol daun bidara arab memiliki warna coklat muda jernih, sedangkan sampel ekstrak etanol rimpang kunyit memiliki warna coklat-merah jernih. Dengan demikian, elektrokoagulasi dapat digunakan untuk menjernihkan ekstrak etanol daun bidara arab dan rimpang kunyit. Kata Kunci: Penjernihan ekstrak, Ziziphus spina-christi, Curcuma longa.